EFFECTS OF PLANT GROWTH REGULATORS ON THE MORPHOGENESIS OF CAULIFLOWER CURD TRANSVERSE THIN CELL LAYER EXPLANTS - Nhựt, Dương Tấn; Vinh, Bùi Văn Thế (Vietnam Journal of Biotechnology, 2011)
Transverse thin cell layers (tTCLs) from mature curd of Cauliflower (Brassica oleracea var. botrytis) were cultured on Murashige and Skoog medium supplemented with different types of plant growth regulators (PGRs) at various concenfrations. The results were recorded after 6 weeks of culture. The presence of 2,4-dichlorophenoxy-acetic acid (2,4-D) at 0.1 - 1.0 mg 1"’ resulted in callus formation, while roots formed in culture medium supplemented with 0.5 - 1.0 mg 1"’ NAA (naphthalene acetic acid). When l-phenyl-3-(l,2,3-thiadiazol-5-yl)-urea (TDZ) was added to culture medium at 0.2 - 0.6 mg 1"’, shoot clusters regenerated directly from the edge of explants. Shoots initiated in the presence of TDZ, but without stem elongation and leaf formation. In order to obtain normal plant development, clumps of regenerated shoots were fransferred onto PGR-free MS medium. Approximately 26 shoots with normal stem elongation developed from each tTCL after 2 weeks. Rootmg was obtained by fransferring shoots to MS medium supplemented with 0.4 mg 1"’ NAA and 0.2 mg r’ Kinetin. Regenerated plants with adventitious roots were fransferred to soil. The results demonsfrated that the choice of PGRs is of significance in determining the morphogenesis of cauliflower curd tTCL explants.